Experimental and Computational Fluid Dynamics: decades of turbulent EFD/CFD complementarity - Bonnet, Jean Paul (Comptes Rendus. Mécanique)
An overview of the parallel evolution of computations and experiments in fluid dynamics in the context of turbulent flows is given, viewed from an experimental side. It is evident that experiments can no longer be seen as only validations for computations and that forecasting for “numerical wind tunnels” is not yet valid. The growing evidence of organized motions in turbulent flows pushes in parallel both experiments and numerical approaches to develop new measurement technologies and numerical methods. Many tools and concepts are shared both by experiments and computations. These approaches appear to be quite complementary and both communities will gain from the mutual fertilization.